A comparison of patient satisfaction (using the BREAST-Q questionnaire) with bilateral breast reconstruction following risk-reducing or therapeutic mastectomy. Issue 9 (September 2018) - Kazzazi, F; Haggie, R; Forouhi, P; Kazzazi, N; Wyld, L; Malata, CM
Summary: Introduction: Patients undergoing mastectomy and immediate breast reconstruction for cancer may be expected to have different perceptions of long-term outcomes compared with those who have this operation prophylactically. Methods: Patients who underwent bilateral mastectomy and breast reconstruction from 2008 to 2014 at the Cambridge Breast Unit were identified from a prospective register and their notes were audited. They were classified according to their indication for surgery as follows: bilaterally therapeutic, bilaterally risk-reducing or combination. The BREAST-Q™ questionnaire was posted to participants using the 'total Dillman method'. Q-SCORE software was utilised to analyse patient satisfaction scores. Results: Sixty-five (58%) responses were received, of which 8 were excluded, leaving 57 usable for the study. The therapeutic group had higher patient satisfaction than the risk-reducing group across most domains including breast, outcome, psychosocial, sexual, physical and information. The combination group scored lower and BRCA gene mutation-positive patients scored the lowest. Physical well-being was maintained across all groups but psychosocial/sexual well-being varied. Good psychosocial well-being was linked to a higher satisfaction with the outcome in the combination and risk-reducing groups. Conclusion: This study highlights the need for clinicians to take into account the indication for surgery as a major psychological factor in patients' perception of self and experience of surgery. It demonstrates that bilateral immediate reconstruction patients report similar physical symptoms irrespective of indication for mastectomy, but the decision-making process in terms of risk-balancing and diagnosis influences satisfaction with self and surgery. It underlines the importance of preoperative management of expectations for patients undergoing risk-reducing procedures.